Morphological features of naevoid melanoma: results of a multicentre study of the International Dermoscopy Society. (5th March 2015) - Longo, C.; Piana, S.; Marghoob, A.; Cavicchini, S.; Rubegni, P.; Cota, C.; Ferrara, G.; Cesinaro, A.M.; Baade, A.; Bencini, P.L.; Mantoux, F.; Mijuskovic, Z.P.; et al.
Summary Background Naevoid melanoma (NeM), a rare variant of melanoma, can be difficult to detect as its clinical and histopathological morphology can simulate a naevus. Objectives To describe the clinical and dermoscopic features associated with NeM. Methods Lesions with a histopathological diagnosis of NeM were collected via an e‐mail request sent to all members of the International Dermoscopy Society. All lesions were histopathologically reviewed and only lesions fulfilling a set of predefined histopathological criteria were included in the study and analysed for their clinical and dermoscopic features. Results Twenty‐seven of 58 cases (47%) fulfilled the predefined histopathological criteria for NeM and were included in the study. Clinically, 16 of the 27 NeMs presented as a nodular lesion (59%), eight (30%) as plaque type and three (11%) as papular. Analysis of the global dermoscopic pattern identified three types of NeM. The first were naevus‐like tumours (n = 13, 48%), typified by a papillomatous surface resembling a dermal naevus. In these lesions local dermoscopic features included irregular dots/globules (46%), multiple milia‐like cysts (38%) and atypical vascular structures (46%). The second type were amelanotic tumours (n = 8, 30%), typified by an atypical vascular pattern (75%). The third type consisted of tumours displaying a multicomponent pattern (n = 4, 15%), characterized by classical local melanoma‐specific criteria. Two lesions (7%) were classified as mixed‐pattern tumours as they did not manifest any of the aforementioned patterns. Conclusions While NeMs may be clinically difficult to differentiate from naevi, any papillomatous lesion displaying dermoscopically atypical vessels and/or irregular dots/globules should prompt consideration for the possible diagnosis of NeM.